THE EFFECTS OF PBL METHOD USING THE HYPERMEDIA TO THE STUDENTS’ CRITICAL THINKING SKILL ON THE SOCIAL STUDIES SUBJECT - Dicky Iranto; S Suparno (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2014)
Education as human’s process to gain knowledge is very important to create thinking skill for the human being. Related to that thing, implemented the learning with Problem Based Learning method which is the learning that is oriented to enhance the students’ critical thinking skill. In the constructivism learning theory, the students should be able to construct the knowledge through problem solving so they got the truth which is useful for the existence. This research is using the quasi experiment method with non-equivalent group design. The conclusion of this research shows that there is enhancement to the students’ critical thinking skill significantly and suggested to use this method on another topic, schools gives the hypermedia facilities, and researching another learning competences. Keywords: Problem Based Learning, Hypermedia, Critical Thinking Skill